Empowering leadership and innovative work behavior: Mediating effect of psychological empowerment - Ritu Yadav; Chand Prakash; Asha Dalal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This empirical investigation primarily aims to measure empowering leadership's impact on innovative work behavior. The study also analyzed the mediating role of psychological empowerment between empowering leadership and innovative work behavior. The structural equation modeling (SEM) technique through AMOS 21 was applied to test the hypothesized relationship between the studied variables over a sample of 438 university employees collected through the snowball sampling technique. The study found that empowering leadership significantly and positively impacted innovative behavior. The mediating effect of psychological empowerment between empowering leadership and innovative work behavior was also significant and positive. The study's findings provide useful directions to stakeholders in framing policies to strengthen their employees' innovative work behavior for the institution's success.
Keywords: 330; Empowering leadership; innovative work behavior; psychological empowerment; academic environment; India